A nitrogen-doped carbon nanotube confined composite material, preparation method and application thereof

The activation of persulfate by nitrogen-doped carbon nanotube boundary composite materials solves the problems of insufficient redox capacity and secondary pollution when degrading PFAS, and achieves a high-efficiency and low-pollution PFAS degradation effect.

CN119386918BActive Publication Date: 2025-04-08SUN YAT SEN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510007317.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-08
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

When traditional carbon nanotube-encapsulated zero-valent iron materials are activated to degrade PFAS, the redox capacity is limited and cannot effectively degrade PFAS. At the same time, there is a problem of secondary pollution caused by iron sludge.

Method used

The nitrogen-doped carbon nanotube domain-limited composite material is used to load iron ions into the carbon nanotube domain-limited structure. By regulating the calcination temperature, nitrogen-doped carbon nanotubes are synthesized in one step to encapsulate the iron carbide domain-limited material, and persulfate is activated to improve degradation efficiency.

Benefits of technology

The material can efficiently degrade PFAS, dyes and antibiotics under low iron ion release and low persulfate concentration, and maintains good degradation performance under neutral and weak alkaline conditions, avoiding secondary contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386918B_ABST
    Figure CN119386918B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of environmental pollution control, and in particular, relates to a nitrogen-doped carbon nanotube confined composite material, a preparation method and application thereof. Compared with the prior art, the present invention uses cheap nitrogen sources and transition metal salts as raw materials, and innovatively synthesizes nitrogen-doped carbon nanotube-wrapped iron carbide confined materials in one step by regulating the cracking temperature, wherein metal nanoparticles are effectively wrapped in carbon nanotubes, and the preparation method is simple to operate, and the prepared material has the advantages of large specific surface area, rich catalytic active sites, efficient electron transfer ability and strong magnetism, and is easy to recycle, so that the nitrogen-doped carbon nanotube confined composite material can effectively improve the electron transfer ability of the material, reduce the binding energy between the material and the persulfate, and enable the reaction system to activate the persulfate mainly through the free radical path, and produce sulfate radicals and hydroxyl radicals with higher redox potential, thereby effectively degrading perfluorinated and polyfluoroalkyl substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental pollution control, and in particular relates to a nitrogen-doped carbon nanotube confined composite material, a preparation method and application thereof. Background Art

[0002] Per- and polyfluoroalkyl substances (PFAS) are a class of fluorinated chemicals widely used in daily life and industrial production. However, since the bond energy of the CF bond in PFAS is extremely high and difficult to break, remediation of water bodies contaminated by PFAS has become a challenging and necessary task.

[0003] In recent years, the advanced oxidation process based on persulfate has developed rapidly. Compared with hydroxyl radicals, sulfate radicals have a longer half-life and a wider range of applications. At the same time, compared with hydrogen peroxide, persulfate is solid, which is easy to transport and store. At present, the main activation methods for persulfate are heating, ultraviolet light, microwave, ultrasound and transition metal activation. Among them, transition metal ion activation is economical and operational, and iron, as a cheap and readily available transition metal, has attracted particular attention. Although the homogeneous system based on Fe²⁺ / persulfate can effectively degrade pollutants, there are problems such as inability to continuously treat and the generation of iron sludge leading to secondary pollution. Heterogeneous catalysis can solve the above problems. Loading transition metals on carriers can effectively prolong catalytic activity and reduce metal ion release. Iron materials based on carbon nanotube confinement are widely used in heterogeneous catalytic systems due to their unique electron transfer characteristics brought about by the confined structure.

[0004] However, due to the restriction of the carbon shell on zero-valent iron, the activation of persulfate by traditional carbon nanotube-wrapped zero-valent iron materials is mainly carried out through non-radical pathways, that is, singlet oxygen is generated ( 1 O2). Although this method can effectively degrade common organic pollutants such as antibiotics and dyes, 1 The extremely limited redox capacity of O2 is unable to effectively degrade PFAS. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a nitrogen-doped carbon nanotube confined composite material, a preparation method and application thereof. The nitrogen-doped carbon nanotube confined composite material exhibits excellent degradation performance when activating persulfate to degrade PFAS, dyes and antibiotics in water, and the leaching amount of iron ions is extremely low.

[0006] The present invention provides a method for preparing a nitrogen-doped carbon nanotube confined composite material, comprising the following steps:

[0007] S1) mixing a first nitrogen source, a second nitrogen source and an iron salt in a solvent, removing the solvent, and obtaining a mixed powder; the first nitrogen source comprises a cyanamide compound and / or a cyanic acid compound; and the second nitrogen source comprises a urea nitrogen source;

[0008] S2) calcining the mixed powder in a protective atmosphere to obtain a nitrogen-doped carbon nanotube confined composite material; the calcination temperature is 630° C. to 1000° C.

[0009] Preferably, the calcination temperature is 630°C to 690°C.

[0010] Preferably, the first nitrogen source is selected from one or more of melamine, cyanuric acid and melamine;

[0011] The urea nitrogen source is selected from one or more of urea, dimethyl urea, diethyl urea, N-acetylphenyl urea, isopropylpyridinium urea and phenyl urea;

[0012] The iron salt is selected from one or more of ferric chloride, ferric nitrate and ferric sulfate.

[0013] Preferably, the mass ratio of the first nitrogen source to the second nitrogen source is 1-3:1-3;

[0014] The mass ratio of the total amount of the first nitrogen source and the second nitrogen source to the iron salt is 1-2:1-3.

[0015] Preferably, the solvent is an alcohol solvent; the ratio of the total amount of the first nitrogen source and the second nitrogen source to the solvent is 1 g: (1.5-20) mL.

[0016] Preferably, the heating rate of calcination in step S2) is 8-10°C / min;

[0017] The calcination is maintained for 1 to 4 hours after reaching the target temperature.

[0018] The present invention also provides a nitrogen-doped carbon nanotube confined composite material prepared by the above preparation method, comprising nitrogen-doped carbon nanotubes; particles are embedded in the tubes of the nitrogen-doped carbon nanotubes; the particles are iron carbide and / or zero-valent iron.

[0019] Preferably, the specific surface area of ​​the nitrogen-doped carbon nanotube confined composite material is 45-106 m 2 / g;

[0020] The nitrogen-doped carbon nanotubes include nitrogen in the form of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen.

[0021] The present invention also provides a method for treating polluted water, comprising the following steps:

[0022] The nitrogen-doped carbon nanotube confined composite material and persulfate are added to polluted water for catalytic degradation.

[0023] Preferably, the polluted water body includes organic pollutants; the organic pollutants include one or more of perfluorinated compounds, dyes and antibiotics.

[0024] The present invention provides a method for preparing a nitrogen-doped carbon nanotube confined composite material, comprising the following steps: S1) mixing a first nitrogen source, a second nitrogen source and an iron salt in a solvent, removing the solvent to obtain a mixed powder; the first nitrogen source comprises a cyanamide compound and / or a cyanic acid compound; the second nitrogen source comprises a urea nitrogen source; S2) calcining the mixed powder in a protective atmosphere to obtain a nitrogen-doped carbon nanotube confined composite material; the calcination temperature is 630°C to 1000°C. Compared with the prior art, the present invention uses cheap nitrogen sources and transition metal salts as raw materials, and innovatively synthesizes nitrogen-doped carbon nanotube-wrapped iron carbide confined materials in one step by regulating the cracking temperature, wherein metal nanoparticles are effectively wrapped in carbon nanotubes. The preparation method is simple to operate, and the precursor is cheap and easy to obtain. The prepared material has the advantages of large specific surface area, abundant catalytic active sites, efficient electron transfer ability and strong magnetism, and is easy to recycle. The nitrogen-doped carbon nanotube confined composite material can effectively improve the electron transfer ability of the material, reduce the binding energy between the material and persulfate, and enable the reaction system to activate persulfate mainly through the free radical path to generate sulfate radicals (SO4· - ) and hydroxyl radicals (•OH), thereby effectively degrading PFAS.

[0025] Furthermore, the present invention obtains carbon nanotube-wrapped iron carbide material by regulating the pyrolysis temperature at 630°C~690°C, which can stably degrade PFAS and various organic matter, effectively avoid the dissolution of metals, and greatly expand the pH value application range of the material, thereby overcoming the technical barrier of low degradation efficiency of traditional zero-valent iron-wrapped carbon nanotube-activated persulfate under neutral and weakly alkaline conditions.

[0026] The experimental results show that the nitrogen-doped carbon nanotube-wrapped iron carbide confined material prepared by the present invention can completely degrade 1 ppm of perfluoro(4-methyl-2-pentenoic acid) in 2 minutes when only 0.2 mM persulfate is added. It also has a good degradation effect on 20 ppm of dyes (rhodamine B) and antibiotics (levofloxacin and tetracycline hydrochloride), and can be used to treat water bodies contaminated by new pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the preparation process of nitrogen-doped carbon nanotube confined composite materials in Examples 1 to 5 of the present invention and Comparative Example 1;

[0028] Figure 2 This is a SEM image of Fe3C@N-CNT obtained in Example 1 of the present invention;

[0029] Figure 3 The Fe obtained in Example 5 of the present invention 0 @SEM image of N-CNT;

[0030] Figure 4 This is a SEM image of Fe@N-CN obtained in Comparative Example 1 of the present invention;

[0031] Figure 5 The Fe3C@N-CNT obtained in Example 1 of the present invention and the Fe3C@N-CNT obtained in Example 5 are 0 BET diagram of Fe@N-CNT and Fe@N-CN obtained in Comparative Example 1;

[0032] Figure 6 The Fe3C@N-CNT obtained in Example 1 of the present invention and the Fe3C@N-CNT obtained in Example 5 are 0 XRD patterns of Fe@N-CNT and Fe@N-CN obtained in Comparative Example 1;

[0033] Figure 7 The Fe3C@N-CNT obtained in Example 1 of the present invention and the Fe3C@N-CNT obtained in Example 5 0 XPS graph of @N-CNT;

[0034] Figure 8 The Fe3C@N-CNT obtained in Example 1 of the present invention and the Fe3C@N-CNT obtained in Example 5 are 0 Raman spectra of Fe@N-CNT and Fe@N-CN obtained in Comparative Example 1;

[0035] Fig. 9 The Fe3C@N-CNT obtained in Example 1 of the present invention and the Fe3C@N-CNT obtained in Example 5 are 0 @N-CNT and Fe@N-CN obtained in Comparative Example 1, the degradation curve of PFMEUPA;

[0036] Fig.10 It is a curve diagram of the degradation of PFMEUPA by M1:U1:Fe2 obtained in Example 1 of the present invention and M1:U3:Fe2 obtained in Example 2;

[0037] Fig.11 It is a curve diagram of the degradation of PFMEUPA by M1:U1:Fe2 obtained in Example 1 of the present invention and M1:U1:Fe6 obtained in Example 3;

[0038] Fig.12It is a curve diagram of the degradation of PFMEUPA by M1:U1:Fe2 obtained in Example 1 of the present invention and M3:U1:Fe2 obtained in Example 4;

[0039] Fig.13 It is a curve diagram of the degradation of PFMEUPA by M1:U1:Fe2 obtained in Example 1 of the present invention and CNT1:Fe1 obtained in Comparative Example 2;

[0040] Fig.14 It is a curve diagram of the degradation of PFMEUPA by M1:U1:Fe2 obtained in Example 1 of the present invention and M2:Fe2 obtained in Comparative Example 3;

[0041] Fig.15 The Fe3C@N-CNT prepared in Example 1 of the present invention and the Fe3C@N-CNT prepared in Example 5 0 @The curve of FMEUPA degradation by N-CNT at different pH values;

[0042] Fig.16 This is a curve diagram of the degradation of dyes and antibiotics by Fe3C@N-CNT prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] The present invention provides a nitrogen-doped carbon nanotube confined composite material, comprising nitrogen-doped carbon nanotubes; particles are embedded in the pipes of the nitrogen-doped carbon nanotubes; the particles are iron carbide and / or zero-valent iron.

[0045] In a specific embodiment provided by the present invention, the nitrogen-doped carbon nanotube confined composite material includes nitrogen-doped carbon nanotubes; particles are embedded in the tubes of the nitrogen-doped carbon nanotubes; and the particles are iron carbide.

[0046] In a specific embodiment provided by the present invention, the diameter of the nitrogen-doped carbon nanotubes is preferably 5-20 nm, more preferably 10-20 nm.

[0047] In a specific embodiment provided by the present invention, the nitrogen-doped carbon nanotubes include nitrogen in the form of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen.

[0048] In a specific embodiment provided by the present invention, pores exist on the surface of the nitrogen-doped carbon nanotube confined composite material.

[0049] In a specific embodiment provided by the present invention, the specific surface area of ​​the nitrogen-doped carbon nanotube confined composite material is preferably 45 to 106 m 2 / g, more preferably 46 to 106 m 2 / g, preferably 60~106 m 2 / g, preferably 80~106m 2 / g, preferably 90~106 m 2 / g, and the most preferred is 100~106 m 2 / g.

[0050] In a specific embodiment provided by the present invention, the Raman spectrum ID / IG of the nitrogen-doped carbon nanotube confined composite material is preferably 0.8-1, more preferably 0.8-0.9, further preferably 0.8-0.87, and most preferably 0.84-0.87.

[0051] The present invention provides a method for preparing a nitrogen-doped carbon nanotube confined composite material, comprising the following steps: S1) mixing a first nitrogen source, a second nitrogen source and an iron salt in a solvent, removing the solvent to obtain a mixed powder; the first nitrogen source comprises a cyanamide compound and / or a cyanic acid compound; the second nitrogen source comprises a urea nitrogen source; S2) calcining the mixed powder in a protective atmosphere to obtain a nitrogen-doped carbon nanotube confined composite material; the calcination temperature is 630°C to 1000°C.

[0052] The present invention does not require the addition of an additional carbon source during the preparation process. Only a nitrogen source and a transition metal salt are used to synthesize the precursor. The nitrogen-doped carbon nanotube-wrapped iron carbide confined material is obtained by calcining in a tubular furnace at a relatively low temperature in one step, and the persulfate can be activated to efficiently degrade perfluorinated compounds, dyes and antibiotics in wastewater. The preparation method has the advantages of simple process, low energy consumption, high yield and abundant nitrogen-containing active sites. In the application of activating persulfate to degrade organic pollutants, the method exhibits the advantages of low persulfate concentration, high degradation efficiency, extremely low iron release and no secondary pollution.

[0053] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0054] The first nitrogen source, the second nitrogen source and the iron salt are mixed in a solvent, and the solvent is removed to obtain a mixed powder; the first nitrogen source is preferably one or more of melamine, cyanuric acid and dicyandiamide; the urea nitrogen source is preferably one or more of urea, dimethyl urea, diethyl urea, N-acetylphenyl urea, isopropylpyridinium urea and phenyl urea; the mass ratio of the first nitrogen source to the second nitrogen source is preferably 1~3:1~3; optionally, the mass ratio of the first nitrogen source to the second nitrogen source is 1:1, 1:2, 1:3, 2:1, 2:3, 3:1 or a range between any two of the above ratios; the iron salt is preferably one or more of ferric chloride, ferric nitrate and ferric sulfate; the mass ratio of the total amount of the first nitrogen source and the second nitrogen source to the mass of the iron salt is preferably 1~2:1~3; optionally, the total amount of the first nitrogen source and the second nitrogen source to the mass of the iron salt The ratio is 1:1, 1:2, 1:3, 2:1, 2:3 or a range between any two of the above ratios; the mass ratio of the first nitrogen source, the second nitrogen source and the iron salt is preferably 1-3:1-3:2-6, more preferably 1-3:1-2:2-5; in some embodiments provided by the present invention, the mass ratio of the first nitrogen source, the second nitrogen source and the iron salt is specifically 1:1:2, 1:3:2, 1:1:6 or 3:1:2; the solvent is preferably an alcohol solvent, more preferably methanol and / or ethanol; the ratio of the total amount of the first nitrogen source and the second nitrogen source to the solvent is preferably 1 g: (1.5~20) mL; optionally, the ratio of the total amount of the first nitrogen source and the second nitrogen source to the solvent is 1 g: 1.5 mL, 1 g: 3 mL, 1 g: 5 mL, 1 g: 10 mL, 1 g: 15 mL, 1 g: 20 mL or a range between any two of the above ratios; the mixing speed is preferably 100~500 rpm, more preferably 200~400 rpm, and more preferably 300 rpm; in the present invention, it is preferred to first mix the total amount of the first nitrogen source and the second nitrogen source with the solvent, and then add the iron salt for a second mixing; the time for the first mixing and the second mixing is each independently preferably 10~60 min, more preferably 20~40 min, more preferably 25~35 min, and most preferably 30 min; after mixing, removing the solvent; the method for removing the solvent is a method well known to those skilled in the art and is not particularly limited. In the present invention, the solvent is preferably removed by drying; the drying temperature is preferably 70°C to 90°C, more preferably 75°C to 85°C, and more preferably 80°C; the drying time is preferably 30 to 60 h, more preferably 40 to 50 h; after removing the solvent, preferably grinding to obtain a mixed powder; the grinding time is preferably 1 to 10 min, more preferably 5 to 8 min.

[0055] The mixed powder is calcined in a protective atmosphere to obtain a nitrogen-doped carbon nanotube confined composite material; the protective atmosphere can be a protective atmosphere well known to those skilled in the art without any special restrictions, and is preferably nitrogen in the present invention; the flow rate of the protective atmosphere is preferably 30-100 mL / min, more preferably 30-80 mL / min, more preferably 40-60 mL / min, and most preferably 50 mL / min; the heating rate of the calcination is preferably 8-10°C / min; the calcination temperature is preferably 630°C-690°C, more preferably 650°C-690°C, and more preferably 680°C-690°C; after the calcination reaches the target temperature, it is preferably maintained for 1-4 h, more preferably maintained for 2-3 h, and more preferably protected for 2 h; after calcination, it is preferably cooled to room temperature, ground, and sieved to obtain a nitrogen-doped carbon nanotube confined composite material; the mesh number of the sieved sieve is preferably 50-200 mesh, more preferably 100-150 mesh.

[0056] The carbon nanotubes prepared by the present invention have a large specific surface area and contain more pore structures, and the metal particles are effectively wrapped in the carbon nanotubes. The crystal structure of iron is an iron carbide alloy, which has better rigidity and catalytic ability; and it is synthesized at a lower temperature (630℃~690℃), which reduces energy consumption and increases yield.

[0057] The present invention also provides a method for treating polluted water, comprising the following steps: adding the nitrogen-doped carbon nanotube confined composite material and persulfate into the polluted water for catalytic degradation.

[0058] In a specific embodiment provided by the present invention, the concentration of persulfate in the catalytic degradation system is preferably 0.1~1 mM; optionally, the concentration of persulfate in the catalytic degradation system is 0.1 mM, 0.2 mM, 0.3 mM, 0.4 mM, 0.5 mM, 0.6 mM, 0.7 mM, 0.8 mM, 0.9 mM, 1 mM or a range between any two of the above values.

[0059] In a specific embodiment provided by the present invention, the concentration of the nitrogen-doped carbon nanotube confined composite material in the catalytic degradation system is preferably 0.01~1 mg / mL; optionally, the concentration of the nitrogen-doped carbon nanotube confined composite material in the catalytic degradation system is 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL or a range between any two of the above values.

[0060] In a specific embodiment provided by the present invention, the polluted water body includes organic pollutants; the organic pollutants include one or more of perfluorinated compounds, dyes and antibiotics.

[0061] In a specific embodiment provided by the present invention, the perfluorinated compound is specifically perfluoro(4-methyl-2-pentenoic acid).

[0062] In a specific embodiment provided by the present invention, the dye is preferably rhodamine.

[0063] In a specific embodiment provided by the present invention, the antibiotic is preferably levofloxacin and / or tetracycline hydrochloride.

[0064] In order to further illustrate the present invention, a nitrogen-doped carbon nanotube confined composite material, a preparation method thereof and applications provided by the present invention are described in detail below in conjunction with embodiments.

[0065] The reagents used in the following examples are all commercially available.

[0066] See also Figure 1 , Figure 1 Schematic diagram of the preparation process of nitrogen-doped carbon nanotube confined composite materials in Examples 1 to 5 and Comparative Example 1.

[0067] Example 1: Preparation of Fe3C@N-CNT (calcination temperature 690°C)

[0068] (1) Take 1.0 g of melamine and urea respectively and put them into a polytetrafluoroethylene beaker. Then add 20.0 mL of anhydrous ethanol with a pipette. Put the rotor into the beaker and stir at 300 rpm on a magnetic stirrer for 30 min to mix them thoroughly. Then add 2.0 g of anhydrous ferric chloride into the beaker and continue stirring for 30 min to fully dissolve it. Finally, an orange-yellow liquid is obtained.

[0069] (2) The orange-yellow liquid obtained in step (1) was placed in a forced air drying oven and dried at 80°C for 48 h to fully evaporate the ethanol, thereby obtaining a brown-yellow solid. The obtained brown-yellow solid was placed in an agate mortar and ground for 5 min to make it uniform, thereby obtaining a brown-yellow powder.

[0070] (3) Take 0.4 g of the brown-yellow powder obtained in step (2) and put it into a corundum crucible, place it in a tube furnace and adjust the nitrogen flow rate to 50 mL / min, leave it for 30 minutes to evacuate the air in the tube furnace. Set the heating rate to 10°C / min, heat from room temperature to 690°C, and then calcine it stably for 2 hours, let it stand to room temperature, grind the obtained black solid in an agate mortar for 3 minutes and pass it through a 100-mesh sieve to obtain a black powder.

[0071] (4) The black powder obtained in step (3) was washed three times with 20 mL ultrapure water and ethanol respectively to remove unstable components on the surface, filtered, and vacuum dried in a vacuum drying oven at 40 °C for 12 h to obtain approximately 0.14 g of nitrogen-doped carbon nanotube confined composite material, recorded as Fe3C@N-CNT or M1:U1:Fe2.

[0072] The Fe3C@N-CNT obtained in Example 1 was analyzed using a scanning electron microscope, and its scanning electron microscope (SEM) image was obtained as follows: Figure 2 As shown. Figure 2 It can be seen that carbon nanotubes have been formed and iron particles are embedded in the tubes, and there are many pores on the surface of the material.

[0073] Example 2: Preparation of M1:U3:Fe2

[0074] In step (1) of this embodiment, 1 g of urea is replaced with 3 g of urea. The other steps are the same as those in embodiment 1. The obtained nitrogen-doped carbon nanotube confined composite material is recorded as M1:U3:Fe2.

[0075] Example 3: Preparation of M1:U1:Fe6

[0076] In step (1) of this embodiment, 2 g of anhydrous ferric chloride is replaced with 6 g of anhydrous ferric chloride. The other steps are the same as those in embodiment 1. The obtained nitrogen-doped carbon nanotube confined composite material is recorded as M1:U1:Fe6.

[0077] Example 4: Preparation of M3:U1:Fe2

[0078] In step (1) of this embodiment, 1 g of melamine is replaced with 3 g of melamine. The other steps are the same as those in embodiment 1. The obtained nitrogen-doped carbon nanotube confined composite material is recorded as M3:U1:Fe2.

[0079] Example 5: Fe 0 @N-CNT preparation (calcination temperature 1000℃)

[0080] In step (3) of this embodiment, the temperature was raised to 1000° C., and the other steps were the same as those in embodiment 1. Finally, about 0.08 g of nitrogen-doped carbon nanotube confined composite material was obtained, which was recorded as Fe 0 @N-CNT.

[0081] The Fe obtained in Example 5 was examined by scanning electron microscopy. 0 @N-CNT was analyzed and its scanning electron microscope (SEM) image was obtained as follows Figure 3 As shown. Figure 3 It can be seen that carbon nanotubes have been formed and iron particles are embedded in the tubes, but the surface of the material is relatively smooth and has basically no pore structure.

[0082] Comparative Example 1: Preparation of Fe@N-CN (calcination temperature 600°C)

[0083] In this comparative example, only the temperature was raised to 600° C. in step (3), and the other steps were the same as those in Example 1. Finally, about 0.16 g of nitrogen-doped carbon nanotube confined composite material was obtained, which was recorded as Fe@N-CN.

[0084] The Fe@N-CN obtained in Comparative Example 1 was analyzed using a scanning electron microscope, and its scanning electron microscope (SEM) image was obtained as follows: Figure 4 As shown. Figure 4 It can be seen that the material has a flaky structure, the surface of the material is relatively smooth, and there is basically no pore structure.

[0085] The Fe3C@N-CNT obtained in Example 1 and the Fe3C@N-CNT obtained in Example 5 0 The specific surface area of ​​the Fe@N-CNT and the Fe@N-CN obtained in Comparative Example 1 was tested by the BET instrument to deduce the specific surface area of ​​the material from the nitrogen adsorption and desorption curve of the material. The BET diagram is as follows: Figure 5 As shown. Figure 5 It can be seen that Fe3C@N-CNT has the largest specific surface area of ​​106 m -2 g -1 , respectively Fe@N-CN and Fe 0 @43.4 and 2.28 times of N-CNT.

[0086] The Fe3C@N-CNT obtained in Example 1 and the Fe3C@N-CNT obtained in Example 5 were analyzed by X-ray diffraction. 0 The XRD patterns of Fe@N-CNT and Fe@N-CN obtained in Comparative Example 1 are shown in Fig. Figure 6 As shown. Figure 6 It can be seen that the iron in Fe3C@N-CNT is mainly iron carbide, Fe 0 The iron in @N-CNT is elemental iron while the iron in Fe@N-CN is amorphous, indicating that efficient synthesis of iron carbide is achieved by adjusting the cracking temperature.

[0087] The Fe3C@N-CNT obtained in Example 1 and the Fe3C@N-CNT obtained in Example 5 were analyzed by X-ray photoelectron spectroscopy. 0 @N-CNT was tested and its XPS graph was obtained as follows Figure 7 As shown. Figure 7 XPS nitrogen peak diagram shows that in Fe3C@N-CNT and Fe 0There are three nitrogen configurations in @N-CNT, namely pyridinic nitrogen (398.40 eV), pyrrolic nitrogen (399.97 eV) and graphitic nitrogen (402.86 eV). Obviously, by adjusting the cracking temperature, the former has more nitrogen-containing active sites, which significantly improves the electron transfer ability of the material.

[0088] The Fe3C@N-CNT obtained in Example 1 and the Fe3C@N-CNT obtained in Example 5 were characterized by Raman spectroscopy. 0 The Raman spectra of Fe@N-CNT and Fe@N-CN obtained in Comparative Example 1 were obtained as shown in the following figure: Figure 8 As shown. Figure 8 It can be seen that Fe3C@N-CNT has the lowest ID / IG, which means it has the highest degree of graphitization compared to the other two materials, and is also beneficial to improving the electron transfer ability.

[0089] Comparative Example 2: Commercial CNT loaded with Fe 0 Preparation

[0090] In step (1) of this comparative example, a total of 2 g of melamine and urea were replaced with 2 g of commercial CNTs. The other steps were the same as those in Example 1. The obtained composite material was recorded as CNT1:Fe1.

[0091] Comparative Example 3: Preparation of M2:Fe2

[0092] In step (1) of this comparative example, a total of 2 g of melamine and urea were replaced with 2 g of melamine. The other steps were the same as those in Example 1. The obtained composite material was recorded as M2:Fe2.

[0093] Example 6

[0094] This example provides the nitrogen-doped carbon nanotube confined composite materials prepared in Examples 1 to 4, and the Fe 0 A performance comparison experiment was carried out on the first catalytic degradation of PFAS in water by using the composite materials CNT1:Fe1 obtained in Comparative Example 2, Fe@N-CNT obtained in Comparative Example 1, and M2:Fe2 obtained in Comparative Example 3.

[0095] It includes the following steps:

[0096] (1) Prepare 200 mL of a 5 mg / L solution of perfluoro(4-methyl-2-pentenoic acid) (PFMEUPA), adjust the pH to 7.0 with 0.1 M hydrochloric acid and 0.15 M sodium hydroxide solution, transfer the solution into a 300 mL conical flask, and add 0.4 mL of the prepared 100 mM persulfate.

[0097] (2) Accurately weigh 10 mg of the nitrogen-doped carbon nanotube confined composite material prepared in Examples 1 to 4, Fe 0 @N-CNT, Fe@N-CN, CNT1:Fe1 and M2:Fe2 were placed in conical flasks respectively and stirred at 300 rpm in a plastic stirrer at room temperature. Samples were taken at certain time intervals to test the concentration. 0 The degradation curves of PFMEUPA by @N-CNT and Fe@N-CN are shown in Fig. 9 As shown; the curves of M1:U1:Fe2 and M1:U3:Fe2 degrading PFMEUPA are shown as Fig.10 As shown; the curves of M1:U1:Fe2 and M1:U1:Fe6 degrading PFMEUPA are shown as Fig.11 As shown; the curves of M1:U1:Fe2 and M3:U1:Fe2 degrading PFMEUPA are shown as Fig.12 As shown; the curve of M1:U1:Fe2 and CNT1:Fe1 degradation of PFMEUPA is shown as Fig.13 As shown; the curves of M1:U1:Fe2 and M2:Fe2 degradation of PFMEUPA are shown as Fig.14 shown.

[0098] Depend on Fig. 9 It can be seen that the degradation rate of PFMEUPA can reach 93% in one minute for Fe3C@N-CNT. 0 @N-CNT and Fe@N-CN only degraded by 60% and 0%, respectively, in one minute.

[0099] Depend on Fig.13 It can be seen that the use of commercially purchased CNTs to replace the original carbon source and nitrogen source increases the preparation cost, and the degradation ability of the prepared material on PFMEUPA is significantly lower than that of Fe3C@N-CNT.

[0100] Depend on Fig.14 It can be seen that if urea is not added during the synthesis process, the degradation ability of the material prepared for PFMEUPA is significantly lower than that of Fe3C@N-CNT, indicating that urea plays a key role in the material formation process.

[0101] The solution was sampled after stirring for 10 min in step (2) to test the concentration of iron ions in the solution. The results showed that the nitrogen-doped carbon nanotube confined composite material prepared in Example 1 released 0.41 ppm of Fe. 0 @N-CNT releases 1.48 ppm, which shows that the nitrogen-doped carbon nanotube confined composite material can effectively avoid the dissolution of metals.

[0102] Example 7

[0103] In this example, the Fe3C@N-CNT prepared in Example 1 and the Fe 0 @N-CNT conducted a comparative experiment on the catalytic degradation of PFAS in water under different pH conditions.

[0104] It includes the following steps:

[0105] (1) The same method as in Example 6 was used except that the pH value of the PFMEUPA solution was adjusted to 3, 5, 7 and 9 using 0.1 M hydrochloric acid and 0.15 M sodium hydroxide solution to obtain Fe3C@N-CNT and Fe 0 The curve of FMEUPA degradation by @N-CNT at different pH values ​​is shown in Fig.15 As shown. Fig.15 It can be seen that Fe3C@N-CNT has a wider pH applicability and can still effectively degrade PFMEUPA in the pH range of 3-9, while Fe 0 @N-CNT can only be effective under acidic pH conditions.

[0106] Example 8

[0107] In this example, the Fe3C@N-CNT prepared in Example 1 was used to perform a catalytic degradation performance test on dyes and antibiotics in water.

[0108] It includes the following steps:

[0109] (1) Rhodamine B (RhB), chlortetracycline hydrochloride (CIP) and levofloxacin (LEV) were used to accurately prepare 200 mL of 20 mg / L solution, and the pH was adjusted to 7.0 with 0.1 M hydrochloric acid and 0.15 M sodium hydroxide solution. The solution was transferred to a 300 mL conical flask, and 0.4 mL of the prepared 100 mM persulfate mother solution was added. Then, 10 mg of the nitrogen-doped carbon nanotube confined composite material Fe3C@N-CNT prepared in Example 1 was added to obtain the degradation curve of dye and antibiotic by Fe3C@N-CNT as shown in the figure. Fig.16 As shown. Fig.16 It can be seen that when Fe3C@N-CNT is used, it maintains excellent degradation efficiency for both high-concentration antibiotics and antibiotics, and the degradation efficiency of RhB and CIP reaches 100% after ten minutes of treatment.

[0110] In summary, the preparation method provided by the present invention has the following advantages:

[0111] 1) The synthesis process of the present invention is a one-step method, and its precursor only needs to fully mix and dry the raw materials, and then heat them in a tube furnace without any additional treatment;

[0112] 2) The present invention will self-assemble and generate nitrogen-doped carbon nanotubes during the calcination process at 630°C to 690°C, so that the material has a huge specific surface area and more active sites, reducing energy consumption.

[0113] 3) In the synthesis process of the present invention, the iron carbide crystal structure and the carbon nanotubes for providing confined packaging are simultaneously generated, and there is no need to use commercial carbon nanotubes to provide confined structures.

[0114] 4) The nitrogen-doped carbon nanotube-wrapped ferrocarbide magnetic material provided by the present invention, wherein the metal particles are wrapped in the carbon nanotubes, overcomes the current problem of secondary pollution caused by metal dissolution, and can completely degrade PFAS within 10 minutes at pH ≤ 9.

[0115] 5) The nitrogen-doped carbon nanotube-wrapped ferrocarbide magnetic material provided by the present invention can maintain excellent degradation efficiency when treating dyes and antibiotics at higher concentrations (20 ppm), while only requiring 0.2 mM persulfate oxidant.

[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a nitrogen-doped carbon nanotube confined composite material, characterized in that: The following steps are involved: S1) mixing a first nitrogen source, a second nitrogen source and an iron salt in a solvent, removing the solvent to obtain a mixed powder; the first nitrogen source comprises a cyanamide compound and / or a cyanic acid compound; the second nitrogen source comprises a urea nitrogen source; the mass ratio of the first nitrogen source to the second nitrogen source is 1-3:1-3; the mass ratio of the total amount of the first nitrogen source and the second nitrogen source to the iron salt is 1-2:1-3; S2) calcining the mixed powder in a protective atmosphere to obtain a nitrogen-doped carbon nanotube confined composite material; the calcination temperature is 630° C. to 690° C.; and the calcination is maintained for 1 to 4 hours after reaching the target temperature; The first nitrogen source is selected from one or more of melamine, cyanuric acid and melamine; The urea nitrogen source is selected from one or more of urea, dimethyl urea, diethyl urea, N-acetylphenyl urea, isopropylpyridinium urea and phenyl urea; The iron salt is selected from one or more of ferric chloride, ferric nitrate and ferric sulfate; The nitrogen-doped carbon nanotube confined composite material comprises nitrogen-doped carbon nanotubes; particles are embedded in the pipes of the nitrogen-doped carbon nanotubes; and the particles are iron carbide.

2. The preparation method according to claim 1, characterized in that: The solvent is an alcohol solvent; the ratio of the total amount of the first nitrogen source and the second nitrogen source to the solvent is 1 g: (1.5-20) mL.

3. The preparation method according to claim 1, characterized in that: The heating rate of calcination in step S2) is 8-10°C / min.

4. The nitrogen-doped carbon nanotube confined composite material prepared by any one of the preparation methods of claims 1 to 3, characterized in that: The invention comprises nitrogen-doped carbon nanotubes; particles are embedded in the pipes of the nitrogen-doped carbon nanotubes; and the particles are iron carbide.

5. The nitrogen-doped carbon nanotube confined composite material according to claim 4, characterized in that: The specific surface area of ​​the nitrogen-doped carbon nanotube confined composite material is 45-106 m 2 / g; The nitrogen-doped carbon nanotubes include nitrogen in the form of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen.

6. A method for treating polluted water, characterized in that: The following steps are involved: The nitrogen-doped carbon nanotube confined composite material prepared by any one of the preparation methods of claims 1 to 3 or the nitrogen-doped carbon nanotube confined composite material according to claim 4 or 5 and persulfate are added to polluted water for catalytic degradation.

7. The processing method according to claim 6, characterized in that: The polluted water body includes organic pollutants; the organic pollutants include one or more of perfluorinated compounds, dyes and antibiotics.

Citation Information

Patent Citations

  • g-C3N4-doped nanotube photocatalyst as well as preparation method and application thereof

    CN114054066A

  • Preparation method and application of nanotube packaged iron particle catalyst

    CN118681585A